Pedagogical Research as a Part of Pre-service Biology Teachers’ Theses - Janštová, Vanda; Novotný, Petr (Scientia in educatione, 2017)
We are hearing many recomendations to teach critical thinking, work with different sources of information, inquiry based teaching and experiment planning. Because the teacher is supposed to transmit these skills to his/her students, it is crucial pre-service teachers should be able to recognize credible sources of information, be critical about information gained and have an idea how pedagogical research is conducted. Although it is not necessary that in-service teachers conduct research, they should know trends which help them to keep their teaching up to date and effective. We conducted a content analysis to find out the focus of pre-service biology teachers’ theses, because we believe such analysing is one of possible ways how to gain an idea about success of pre-service teachers’ preparation. We analysed all theses (n = 199) defended at our home departments in last three years and compared the theses of pre-service teachers from each faculty. Pedagogical research was a part of 60 theses, the most frequently used tool for acquiring data was a questionnaire. A number of theses failed to describe respondent selection. Pre-service teachers from the two departments differed e.g. in the extent of inductive statistics usage. Results are discussed and steps to improve suggested.